PRIMARY HYDATID DISEASE OF CHEST WALL - Ullah, Rahman; Ullah, Irfan; Nazir, Mashal; Raza, Syed Shahmeer; Janan, Hassan; Khan, Najeebullah; Hijaz, Asfandiar Shah Rukh; Khan, Muhammad Babar; Shah, Aimal; Bashir, Gulsam (Journal of Ayub Medical College Abbottabad, 2020)
Hydatid disease-a parasitic medical condition caused by echinococcus, is one of the oldest diseases known to mankind. Primary hydatid disease of the chest wall is very rare and only nine cases have been reported so far in the literature. This study presents a case of primary hydatid chest wall in a patient with right infraclavicular swelling that increased in size suddenly. A 35 year-old lady presented to the Surgical Unit of Khyber Teaching Hospital with a two and a half year history of right infraclavicular chest wall lump which increased in size abruptly Upon investigation the Computed tomographic scan of the chest showed a complex multiseptated hypodense lesion in the right pectoralis muscle with no involvement of underlying clavicle or rib. She was booked for exploration under general anaesthesia electively. The lump revealed multiple daughter cysts with the characteristics of germinal layers and ecto cysts of hydatid cysts. The patient had a stable recovery in the postoperative period and was sent home on medical treatment. On follow up she was fine; the wound had healed and there was no swelling in the surgical site. Primary hydatid disease of the chest wall is a very rare disease, so this case is a piece of good evidence to consider hydatid cyst in the differential diagnosis of any cystic mass in any part of the body, especially in endemic areas. Radical peri-cystectomy followed by chemotherapy with albendazole is all that is needed for the treatment. Keywords: Primary Hydatid Disease; Dog Tapeworm; ecto cysts; Echinococcus granulosus